Evaluation of the adequacy of diflubenzuron and dechlorane in toxic baits for leaf-cutting ants (Hymenoptera : Formicidae) based on formicidal activity - Nagamoto, Nilson S.; Forti, Luiz Carlos [UNESP]; Raetano, Carlos Gilberto [UNESP] (Springer, 2007)
Studies assessing the characteristics of active ingredients (AIs) of toxic baits for leaf-cutting ants are still scarce, although the need for a delayed action of these compounds on adult workers has been well accepted (mortality <= 15% at 24 h and <= 90% at 21 days). Therefore, we determined the insecticidal action of two AIs used in commercial baits, diflubenzuron and dechlorane, over time in workers, and discussed the control of colonies in relation to the existing literature. Dechlorane presented excellent insecticidal activity with a delayed action at all concentrations tested, although its commercial use has been prohibited due to its organochlorine nature. In contrast, diflubenzuron did not cause significant mortality or symptoms of intoxication, indicating that the successful cases reported with the use of baits containing this AI were in fact due to an accidental contamination with dechlorane. We comment about the ineffectiveness of diflubenzuron on alternative targets, i.e., young forms and the mutualistic fungus, supporting the concept that the AI needs to a have a delayed action on adult workers.
Keywords: Atta sexdens rubropilosa; dechlorane; delayed action; diflubenzuron; leaf-cutting ant; toxic bait